Synthesis of Hydrocarbon Through Pyrolysis of Used Lubricant with CaO - Endar Puspawiningtiyas; Renaldi Kuntara (Universitas Muhammadiyah Purwokerto, 2023)
The processing of used lubricants by pyrolysis with CaO was carried out. Pyrolysis was carried out at 375°C using a glass reactor. The effect of pyrolysis time and the addition of CaO on the pyrolysis of used lubricants was investigated. A SimDis (Simulated Distillation) analyzer is used to analyze the hydrocarbons of the pyrolysis products, while AAS is used to analyze the metal content. The results show that the addition of CaO to lubricating oil has an effect on increasing the yield, reducing the density, reducing the specific gravity, reducing the viscosity, reducing the metal content, reducing the acid number and increasing the recovery of the diesel/petrol content in hydrocarbons. The longer time during the pyrolysis process affects higher yield, higher density, higher specific gravity, higher viscosity, lower metal content and lower acid number. The results of the hydrocarbons obtained are 3 components, namely gasoline, aviation fuel and diesel. The dominant products of pyrolysis of used lubricants without CaO are diesel-type hydrocarbons (44.4%) and gasoline-type hydrocarbons with CaO (45.9%). The best results were obtained for waste oil samples with the addition of CaO, giving a yield of 72%, a density of 858.8 kg/m3, a specific gravity of 0.86, a viscosity of 17.01 cStokes, a Pb metal content of 0.522 mg/L and a Cu metal content of 0.292 mg/L. L, acid number 1.08 mg KOH/g, Simdis 44.38% diesel.